2003
DOI: 10.1002/eat.10225
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating and binge eating disorder in a small‐scale, indigenous society: The view from Fiji

Abstract: Objective: Although the cross-cultural prevalence of anorexia and bulimia nervosa has been investigated in multiple studies, little is known about the prevalence and correlates of binge eating and binge eating disorder (BED) cross-culturally. No published studies to date have explored BED in small-scale, indigenous, or developing societies. The current study investigated the prevalence and correlates of binge eating in a community sample of Fijian women living in rural Fiji. Methods: Fifty ethnic Fijian women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
(37 reference statements)
1
19
0
1
Order By: Relevance
“…This hypothesis has received support from studies of exposure to Western popular media in Fiji (Becker et al, 2002; Becker et al, 2003; Becker et al, 2011). Some studies have compared non-representative samples from related Western and non-Western populations, finding mixed support.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This hypothesis has received support from studies of exposure to Western popular media in Fiji (Becker et al, 2002; Becker et al, 2003; Becker et al, 2011). Some studies have compared non-representative samples from related Western and non-Western populations, finding mixed support.…”
Section: Discussionmentioning
confidence: 98%
“…Cultural differences in eating habits and body image ideals have been hypothesized to affect risk for eating disorders, with greater emphasis on control of eating and value of thinness hypothesized to lead to higher prevalence of eating disorders in Western countries (Becker et al, 2002; Becker, Burwell, Navara, & Gilman, 2003; Becker et al, 2011; Lynch, Heil, Wagner, & Havens, 2007; Mousa, Al-Domi, Mashal, & Jibril, 2009; Toro et al, 2006). This hypothesis has received support from studies of exposure to Western popular media in Fiji (Becker et al, 2002; Becker et al, 2003; Becker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Restraint may trigger binge eating when breaking strict dietary rules results in disinhibited eating [24]. In support of this model, several authors found a strong correlation between body dissatisfaction and binge eating [25], and moreover, there is clear evidence linking binge eating and a history of dietary restraint [6,19,26,27]. In a 10-year longitudinal study, Goldschmidt et al [10] confirmed that dieters were at higher risk for binge eating onset than nondieters.…”
Section: Introductionmentioning
confidence: 95%
“…10,21 Culturally sanctioned overeating-sometimes associated with distress-as well as purging in this society in the absence of indigenous recognition of illness suggest that variation in universal behaviors may sometimes be recognized as symptoms only in relation to the social context. 22 In addition, there is an indigenous category-commonplace in Pacific societies, but without a clear analog in Western biomedical nosology-for an appetite disorder (macake, Fijian) which is characterized by poor appetite and food refusal and arouses intense social concern and intervention, 10 but otherwise bears little resemblance to any DSM established eating disorder. Individuals with macake are characteristically distressed by the poor appetite and generally willingly take prophylactic or therapeutic doses of traditional herbal medicines to restore appetite.…”
Section: Cross-cultural Variation In Illness Experience and Presentationmentioning
confidence: 99%